2003
DOI: 10.1002/zoo.10070
|View full text |Cite
|
Sign up to set email alerts
|

Contribution to the welfare of captive wolves (Canis lupus lupus): A behavioral comparison of six wolf packs

Abstract: An interesting way to understand and eventually improve the well-being of captive animals is to compare different living and social conditions, in order to analyze the behavioral differences between animals living in very restrictive conditions and animals enjoying more permissive ones. In the present study we performed 10 observations of six wolf enclosures with quite different living and social conditions. The rest/activity balance, behavioral diversity, and use of available space were used as welfare criter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 21 publications
0
18
0
Order By: Relevance
“…Species that experienced an increase in behavioral diversity following enrichment or an enhanced habitat included big cats [ 27 , 45 , 46 ], leopard geckos [ 38 ], parakeets [ 33 ], capuchins [ 40 ], African cichlid males [ 47 ], pigs [ 21 , 48 , 49 , 50 ], wombats [ 39 ], red foxes [ 51 ], bottlenose dolphins [ 52 ], ghost bats [ 53 ], bears (spectacled [ 30 ], Andean, sloth, brown, and black [ 54 ]), rats [ 55 ], African elephants [ 32 ], small felids [ 26 ], hognose snakes [ 56 ], giant pandas [ 28 , 29 ], and chimpanzees [ 31 ]. Species where enrichment or improved habitat was not found to significantly change behavioral diversity include armadillos, bush babies, and two toed sloths [ 57 ], wolves [ 58 ], African elephants [ 59 ], zebra fish and checker barbs [ 60 ], and lions [ 41 ]. However, some of the species where enrichment did not increase behavioral diversity overlap with species were enrichment did increase behavioral diversity, so it could be the type or timing of the enrichment that is impacting the significance of results [ 61 ].…”
Section: Factors Affecting Behavioral Diversitymentioning
confidence: 99%
See 1 more Smart Citation
“…Species that experienced an increase in behavioral diversity following enrichment or an enhanced habitat included big cats [ 27 , 45 , 46 ], leopard geckos [ 38 ], parakeets [ 33 ], capuchins [ 40 ], African cichlid males [ 47 ], pigs [ 21 , 48 , 49 , 50 ], wombats [ 39 ], red foxes [ 51 ], bottlenose dolphins [ 52 ], ghost bats [ 53 ], bears (spectacled [ 30 ], Andean, sloth, brown, and black [ 54 ]), rats [ 55 ], African elephants [ 32 ], small felids [ 26 ], hognose snakes [ 56 ], giant pandas [ 28 , 29 ], and chimpanzees [ 31 ]. Species where enrichment or improved habitat was not found to significantly change behavioral diversity include armadillos, bush babies, and two toed sloths [ 57 ], wolves [ 58 ], African elephants [ 59 ], zebra fish and checker barbs [ 60 ], and lions [ 41 ]. However, some of the species where enrichment did not increase behavioral diversity overlap with species were enrichment did increase behavioral diversity, so it could be the type or timing of the enrichment that is impacting the significance of results [ 61 ].…”
Section: Factors Affecting Behavioral Diversitymentioning
confidence: 99%
“…As previously mentioned, training of bottlenose dolphins was found to significantly increase behavioral diversity [ 37 ]. Social housing and group living were found to relate to behavioral diversity in tamandua [ 36 ] and wolves [ 58 ]. Alternatively, social management was not found to relate to behavioral diversity in Asiatic lions [ 22 ].…”
Section: Factors Affecting Behavioral Diversitymentioning
confidence: 99%
“…They found that wolves living in the ''non-enriched'' environments had higher activity and aggression levels. Frezard and Le Pape [2003] found that wolf packs living in larger, more ''naturalistic'' enclosures used less available space and spent more time resting. It is common knowledge that wolves in the wild spend a majority of their time resting, conserving energy until the next meal.…”
Section: Discussionmentioning
confidence: 99%
“…During each hour of observation, the behaviour of each wolf was recorded every 1 min. The ethogram comprised 16 behavioural categories (Table 1) and was obtained by integrating behaviours described in scientific literature [5,18,32,33,34] with direct behavioural observations over a 7-day period, prior to the study. Since behavioural data from the first observation session on 29 March 2017 had not been recorded, data from the entire day were eliminated.…”
Section: Methodsmentioning
confidence: 99%